Design Virtual Instrumentation System of a Cigarette Smoke Detector - Sabar; Joni; Kisna Pertiwi; Ratih Rundri Utami; Sastra Kusuma Wijaya (PT FORMOSA CENDEKIA GLOBAL, 2022)
The contributor to air pollution today is cigarette smoke because almost every public facility is provided with a special room for smokers and a non-smoking room. However, the level of awareness of active smokers is not only harmful to themselves but also to secondhand smoke, especially in smoke-free environments. Along with the development of technology, we can take advantage of the development of a cigarette smoke detector based on the Arduino with the MQ-2 gas sensor. Therefore, this tool will make it easier to monitor a crowded room for cigarette smoke. The system uses the MQ-2 gas sensor to detect cigarette smoke in a room. By using a buzzer alarm as a sign that there is cigarette smoke inside a room. The ppm value obtained from the sensor is 550 ppm on the cigarette sensor to detect cigarette smoke